Model sistem antrian multi channel single phase dalam mengevaluasi kinerja instansi (Studi kasus: Rumah Sakit Umum Pindad Turen) - Idah, Linatul Af; Tarigan, Asmara Iriani; Idayani, Darsih (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2024)
Queues usually occur because the number of consumers served exceeds capacity. Pindad General Hospital is a hospital that provides patient services and there are often queues to provide services. Pindad General Hospital has three service facilities with one queue, such as the Multi Channel Single Phase (MCSP) queuing process by implementing First Come First Served (FCFS) queuing. This research aims to analyze queuing methods and model the queuing system that occurs in the service section of Pindad General Hospital as a material study to evaluate the performance system at Pindad General Hospital. Data collection was carried out by observing the receptionist service. The data analysis was carried out by testing the distribution of patient arrivals and services to patients using the Kolmogorov Smirnov Test and conducting a steady state condition test. Then proceed with analyzing the data using the MCSP queuing system model to evaluate performance using the SPSS application. The results show that the queuing system modeling applied by Pindad General Hospital is the model. The three service facilities that are available really help the service performance at Pindad General Hospital, so there is no need for additional service facilities.